1949
DOI: 10.1021/ja01170a074
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of N-Methylol, N-Alkoxymethyl and N-Alkylthiomethyl Polyamides

Abstract: The pyrolysis method used previously to transform the acetyl derivatives of N,N-dimethyllactamide into , -dimethylacrylamide was applied to the preparation of other N-alkyl acrylamides and methacrylamides. N,N-Diethylacrylamide was obtained in good yield by the thermal decomposition of N,N-diethyl-a-acetoxypropionamide, but pyrolysis of N-methyl-and N,N-di-ro-butyl-acetoxypropionamide was less satisfactory for the preparation of the corresponding acrylamides.N-Methyl-and N,N-dimethylmethacrylamides were made s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

1961
1961
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Cairns et al [41] synthesised polyamides that can be converted to the N-mercaptomethyl form by redox reactions with formaldehyde, but it took until 1995 for the first electrochemical study of polyamides to be conducted by Tsutsumi et al [42], who also continued studying the electrochemical behaviour of polyamide-containing disulphide bonds [43] in 1996. A year later, in 1997, Agrawal et al [44] prepared EC polymeric solid films from in situ electromagnetic radiation of a low viscosity EC monomer, which includes polyamides.…”
Section: Polyamides (Pas)mentioning
confidence: 99%
“…Cairns et al [41] synthesised polyamides that can be converted to the N-mercaptomethyl form by redox reactions with formaldehyde, but it took until 1995 for the first electrochemical study of polyamides to be conducted by Tsutsumi et al [42], who also continued studying the electrochemical behaviour of polyamide-containing disulphide bonds [43] in 1996. A year later, in 1997, Agrawal et al [44] prepared EC polymeric solid films from in situ electromagnetic radiation of a low viscosity EC monomer, which includes polyamides.…”
Section: Polyamides (Pas)mentioning
confidence: 99%
“…These chains pack together so that the oxygen atoms of one molecule are opposite the -NH groups of an opposite molecule providing abundant opportunity for the formation of hydrogen bonds between adjacent chains. This results in very high interchain forces [2]. It was subsequently found that by chemically modifying these nylons a wide variety of polymers could be produced with vastly different properties from the parent nylons.…”
Section: Poly Ami Desmentioning
confidence: 99%
“…The commonest modified nylons are N-alkoxymethyl derivatives [22]. These are produced when nylons are reacted with formaldehyde and an alcohol or mercaptan in the presence of an acid to substitute alkoxymethyl groups on the nitrogen atom [2,3]:…”
Section: Poly Ami Desmentioning
confidence: 99%
“…E arly work by Cail'l1s and coworkers [4,5] describ ed the prep aration and so me properties of Nm ethylol, N-alkoxymethyl, and N -alkylthiom ethyl polyamides. Al though th ese reactions were carried out while the polymers were in the dissolved state, they are of interest as potential precursors for crosslinking.…”
Section: Introduction Of Intermolecular Disulfide Crosslinksmentioning
confidence: 99%
“…of strong acids, producing an N -methoxy-methylated polycaprolactam (II). Th e structure of t hi s product has already been es tablished [4] from the facts (a) N -m ethoxy-methyl ated polyamides produce form aldehyde in good agreement with the expected quantities predicted from m ethoxyl analyses, (b) polyarnides prepared from N,N'-alkylated diamines do not r eact wi th the hemiacetal of form aldehyde and methyl alcohol, and (c) infrared absorption spectroscopy indicates a substantial decr ease in th e intensity of cer tain -NH absorption bands in th e N -methoxy methylated polyamides.…”
Section: Introduction Of Intermolecular Disulfide Crosslinksmentioning
confidence: 99%